2020
DOI: 10.1021/acs.analchem.9b05651
|View full text |Cite
|
Sign up to set email alerts
|

Field Induced Fragmentation (Fif) Spectra of Oxygen Containing Volatile Organic Compounds with Reactive Stage Tandem Ion Mobility Spectrometry and Functional Group Classification by Neural Network Analysis

Abstract: Mobility isolated spectra were obtained for protonated monomers of 42 volatile oxygen containing organic compounds at ambient pressure using a tandem ion mobility spectrometer with a reactive stage between drift regions. Fragment ions of protonated monomers of alcohols, acetates, aldehydes, ketones, and ethers were produced in the reactive stage using a 3.3 MHz symmetrical sinusoidal waveform with an amplitude of 1.4 kV and mobility analyzed in a 19 mm long drift region. The resultant field induced fragmentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
0
12
1
Order By: Relevance
“…The precision (PRE), recall (REC), F1 score (F1,) and accuracy (ACC) are used to evaluate the results. 46 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The precision (PRE), recall (REC), F1 score (F1,) and accuracy (ACC) are used to evaluate the results. 46 …”
Section: Methodsmentioning
confidence: 99%
“…The precision (PRE), recall (REC), F1 score (F1,) and accuracy (ACC) are used to evaluate the results. 46 The calculation formula of PRE is eq 6: where TP is a true positive case; that is, the actual case is a positive case, and the model prediction is a positive case. FP is a true negative case; that is, the actual case is a negative case, and the model prediction is a negative case.…”
Section: X Ymentioning
confidence: 99%
“…Wang et al identified many components in Lanqin Oral Liquid (a Chinese patent medicine) by UPLC-IM-QTOF-MS and automatic peak annotation driven by UNIFI software. The CCS data correlation global natural products molecular networking platform (GNPS) can further identify targeted or nontargeted compounds with a high throughput. …”
Section: Applications Of Im-ms For the Separation And Characterizatio...mentioning
confidence: 99%
“…Shokri et al expanded on this concept by combining multistage IMS separation with a fragmenter grid operated with a high-frequency sinusoidal electric field, allowing prior mobility selection of the ions to be fragmented . It could be shown that the mobility analysis of fragments enables the identification of chemical classes via IMS . Further improvements of design and operation methods results in the highly efficient ion manipulator presented in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Imparting energy into the ion-neutral system can additionally influence the equilibrium of chemical reactions and lead to cluster dissociation or even fragmentation and thus to the formation of new ion species related to the target substance . IMS systems take advantage of increased ion energies including the high kinetic energy ion mobility spectrometer (HiKE-IMS) from the study of Langejürgen et al, , the tandem IMS with field-induced fragmentation from the study of Shokri et al, and the field asymmetric time of flight IMS (FAT-IMS) from our group first published in 2015, which is the fundamental basis for this work. The ions’ energy, expressed as an effective temperature T eff , is according to the Wannier expression proportional to the square of the reduced electrical field strength E / N .…”
Section: Introductionmentioning
confidence: 99%